Small cell carcinoma of cervix: A population-based study evaluating standardized provincial treatment protocols - Soumyajit Roy; Jenny J. Ko; Gaurav Bahl (Elsevier, 2019)
Objectives: To describe the patient characteristics, patterns of treatment, and outcome of patients with small cell carcinoma of Cervix (SmCC) treated with radical radiotherapy from a provincial cancer registry database. Methods: Overall 25 patients with SmCC were treated with radical radiotherapy (with or without chemotherapy) from January 1, 1994 to December 31, 2013. Nineteen patients had pure SmCC while 6 had additional neuroendocrine component. Patients were treated with combined chemo-radiotherapy using multi-agent chemotherapy with pelvic or combined pelvic and para-aortic radiotherapy. All patients received brachytherapy. Use of prophylactic cranial irradiation was dependent on physician discretion. Survival was estimated using Kaplan-Meier method and compared using log-rank test. Results: We report a median overall survival of 53.8 months for our cohort. After a median follow-up of 54 months for surviving patients, the overall survival (OS) and progression free survival (PFS) at 5-years were 48% and 46.4% respectively. Patients with stage I-IIA disease had superior 5-year PFS (67.3% vs. 11.1%; p = .004) and 5-year OS (62.5% vs. 22.2%; p = .006). Patients with node-negative disease had a trend towards better 5-year PFS (55.7% vs. 19%; p = .07) and OS (61.1% vs. 14.3% at 5-years; p = .06) Distant metastasis was the predominant site of disease progression (n = 12; 48%). Conclusion: Distant metastasis is the predominant pattern of failure for patients with SmCC treated with radical chemo-radiotherapy. With modern chemo-radiotherapy protocols we can expect a 5 year survival of around 50%. Early stage and node-negative status appear to be favorable prognostic factors with survival rates at 5-year over 60%. Keywords: Small cell carcinoma of cervix, Chemo-radiotherapy, Platinum-based chemotherapy and external beam radiotherapy, Distant failure, Stage, Nodal involvement